Culinary Tourism Experience in Prawirotaman-Tirtodipuran, Yogyakarta - Saraswati, Kevin Dea; Marciallia, Syan Rachma; Manifesty, Odilia Renaningtyas (Jurnal Ilmiah Hospitality Management, 2025)
Culinary tourism is a key attraction in the tourism industry. It offers a range of food, cultural, social, and environmental experiences for visitors. This study analyzes the culinary tourism experience in Yogyakarta’s Prawirotaman-Tirtodipuran area. The research used a descriptive quantitative method and distributed questionnaires to tourists. The analysis focused on four variables: gastronomic food experience, cultural experience, social experience, and environmental experience. Findings indicate that most respondents gave high scores, primarily in categories 4 (agree) and 5 (strongly agree), on a 1-5 Likert scale. The gastronomic food experience received the highest scores, particularly in terms of enjoyment and variety of food options. Social and cultural experiences followed, enhancing engagement with the local community. The environmental experience stood out for its comfortable facilities and dining atmosphere. Overall, the area shows strong potential as a leading culinary destination in Yogyakarta.